Perancangan Sistem Tempat Sampah Pintar Dengan Sensor HCRSF04 Berbasis Arduino UNO R3 - Anus Wuryanto; Nunung Hidayatun; Mia Rosmiati; Yusnia Maysaroh (LPPM Universitas Bina Sarana Informatika, 2019)
Every day humans produce waste, both household and industrial waste that has various forms and types. Garbage can be a problem because it interferes with human health, causing foul odors and air pollution. The awareness of disposing of garbage in its current place is considered to be very lacking. This is because trash cans are still using a simple method that is by manually opening and closing the trash can. This will cause the hands to be very vulnerable to bacteria from garbage. In this study, it was explained how to design smart bins that could function to attract the public in general and students of SDN Tridayasakti 02 Tambun Selatan to dispose of their places using Arduino Uno R3. Another benefit is to make people aware of the importance of health by removing trash. The method used to detect this object is the method of racang bangun which consists of several stages, namely (1) Needs Analysis, (2) Design, (3) Implementation of the Series, (4) Testing Tools.